Evaluation of current sensitivity of quantum flux parametron. (4th July 2017) - Yamanashi, Yuki; Matsushima, Takashi; Takeuchi, Naoki; Yoshikawa, Nobuyuki; Ortlepp, Thomas
Abstract: Current sensitivity of a quantum flux parametron (QFP) was evaluated by measuring gray zone width on the basis of both circuit simulation and measurements, for superconducting sensing systems composed of a superconducting sensor array and superconducting read-out and signal processing circuits. Simulation results indicate a narrow gray zone width can be obtained by decreasing inductances comprising the QFP. Moreover, both high-sensitivity and low-power operation of the QFP can be realized by using optimized circuit parameters with an excitation current that has long rise time. A gray zone width of approximately 0.5 μ A, which is smaller than that of the Josephson current comparator based on a single flux quantum circuit, was obtained experimentally, using a trapezoidal excitation current with rise time of 50 μ s. These results indicate the QFP is promising for the read-out circuit in superconducting sensing systems, due to its high sensitivity and low power consumption.